Effect of multi-layer laser cladding of Stellite 6 and Inconel 718 materials on clad geometry, microstructure evolution and mechanical properties. (September 2021) - Thawari, Nikhil; Gullipalli, Chaitanya; Katiyar, Jitendra Kumar; Gupta, T.V.K.
Abstract: The multi-layer laser cladding of high temperature resistance alloys i.e., Stellite 6 and Inconel 718 on SS316 was developed with an objective to investigate the effect of cladding materials on clad geometry, microstructure evolution and mechanical properties. The analysis was performed using Optical Microscope, SEM with EDS and Microhardness tester respectively. The results have shown a comparable difference in all the aspects of study. A 50% and 30% increment in clad height is measured while cladding at 12 mm/s and 16 mm/s scan speed as compared to 20 mm/s for both the alloys. The Inconel 718 deposits has shown 15–25% larger clad height, than Stellite 6. Also, under varying process parameters, 15–45% penetration depth and 10–15% higher dilution in Inconel 718 is obtained. SEM results have revealed that the microstructure evolution from top to bottom of the clad is nearly the same except at low laser powers. The decrement in microhardness is observed near the interface due to dilution and is higher in the first layer than the second layer. Whereas, the low dilution obtained in the second layer is because of the newly deposited layer over the substrate. The present work has given the optimum parameters (laser power and scan speed) as 2900 W and 20 mm/s for Stellite 6 and 3400 W, 12 mm/s for Inconel 718 respectively. Highlights: Multilayer deposition Stellite 6 and Inconel 718 alloy is performed successfully using Laser Cladding process. Effect of Stellite 6 and Inconel 718 with process parameters, on geometry, microstructure and microhardness is studied. Inconel 718 deposits shown 15−25% higher clad heights, 15–45% penetration depth, 10–15% dilution than Stellite 6. Both alloy cladding shown columnar grain formation at interface and converts to equiaxed near top surface region. Low laser powers and high scan speeds are not suitable for cladding Inconel 718 powders as compared to Stellite 6.